MULTI-SCALE EEG FEATURE DECODING WITH SWIN TRANSFORMERS FOR SUBJECT INDEPENDENT MOTOR IMAGERY BCIS - Qamar, Wasi Ur Rehman (Nazarbayev University School of Engineering and Digital Sciences, 2025)
High inter-subject variability and the non-stationary nature of EEG signals pose significant challenges for subject independent Brain Computer Interfaces (BCIs) leading to poor model generalization. Differences in neural activity patterns, electrode placements, and external noise further degrade performance making it difficult to develop BCIs that remain reliable across users without extensive recalibration. This study presents a Compact Convolutional Swin Transformer (CCST) to address this issue by utilizing hierarchical window based self attention combined with convolutional feature extraction to efficiently capture both local electrode interactions and global temporal dependencies. This multi-scale feature representation enhances generalization across subjects, a critical factor for real-world BCI deployment. CCST was evaluated on the BCI Competition IV (2a and 2b) datasets using Leave-One-Subject-Out (LOSO) cross validation and state-of-the-art classification accuracies of 76.74% and 74.06% were achieved respectively. Statistical analysis using the Wilcoxon signed rank test with Bonferroni correction confirms significant performance improvements over TCN, TIDNet, and Deep4Net. Additionally, CCST achieves a 2 times reduction in parameters and a 2% decrease in FLOPs compared to full self attention models making it more efficient for real-time BCI applications. These results establish CCST as a scalable and efficient framework for adaptive, subject-independent BCIs with promising applications in neurorehabilitation, assistive technology, and cognitive training.
Keywords: Brain Computer Interface; Motor Imagery; Deep Learning; EEG; Swin Transformer; type of access: embargo